Efficacy of Single Dose of 800µg Vaginal Misoprostol in the Induction of First Trimester Abortion - Arjamand Mahmood, Amina Saleem, Salma Khalid, Safoora Anjum, Ummay Ammara, Shazia Noor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dissolution of pregnancy in the first trimester for several maternal as well as foetal concerns (therapeutic abortion) is a common obstetrical issue. However, induction of abortion demands thorough and effective care, just as women in labour with childbirth. World Health Organization estimates that 13% of all the maternal deaths in South-Asia are associated with abortion procedures. The current recommended approach is 800 µg misoprostol administered vaginally repeated at 3 hours intervals for a maximum of 3 doses with a reported frequency of 85% for complete expulsion of products of conception within 24 hours after administration. There are studies which claim a single vaginal dose of 800µg misoprostol to be equally effective, but more convenient and safe. However, there was controversy surrounding the efficacy of this single dose regimen. Aim: To determine the efficacy of single dose of 800 µg vaginal misoprostol in the induction of first trimester abortion. Methods: This was a descriptive case series conducted at the Department of Obstetrics and Gynecology, University of Lahore Teaching Hospital, Lahore. A written informed consent was taken from all the patients. Results: The total number of patients admitted in the unit over period of 1 year were 369 women in their first trimester requiring therapeutic abortion. The mean age of the patients was 29.04±4.98 years and the mean gestational age was 7.96±2.24 weeks. Majority of the patients were para 2 48(40.1%) followed by para 3(35.8%) and para 1(24.1%). Complete expulsion of POCs within 24 hours was achieved in 342(92.7%) cases while it failed in 7.3% cases. When cross tabulated, the frequency of successful expulsion was unaffected by age (p=.114), gestational age (p=.250) and parity (p=.238). Conclusion: The frequency of complete expulsion of products of conception with single dose of 800µg vaginal misoprostol in first trimester induced abortion was observed to be 92.7%.